El amigo de la muerte - Alarcón, Pedro Antonio de, (www.linkgua-digital.com, 2019)
Pedro Antonio de Alarcón created a satirical newspaper, wrote plays, and reported from the war in Africa. He completed many travel writings and eventually became politically involved, becoming Senator and Ambassador to Norway and Sweden. His prolific literary career reflects the development of Realism with some residual influences from the Romantic Era.